Profound Immunosuppression with Reversed CD4:CD8 Ratio in a Tuberculosis Patient with Acquired Immunodeficiency Syndrome: A Case Report - Doan Atrya; Efrida (HM Publisher, 2025)
Background: The co-occurrence of tuberculosis (TB) and acquired immunodeficiency syndrome (AIDS) presents a formidable clinical challenge due to the synergistic impact on the immune system. This case report describes a patient with TB/AIDS co-infection exhibiting profound immunosuppression characterized by a severely diminished CD4 count and an unusual reversal of the CD4:CD8 ratio. Case presentation: A 39-year-old male presented with symptoms indicative of both TB and advanced HIV infection, including shortness of breath, weight loss, and oral thrush. Physical examination revealed bilateral lung crackles. Laboratory investigations confirmed pulmonary TB and revealed a critically low CD4 count (6 cells/µL), and a CD8 count of 71 cells/µL, resulting in a reversed CD4:CD8 ratio of 0.08. The patient's HIV viral load was markedly elevated at 598,403 copies/mL. This case underscores the complex interplay between TB and HIV, highlighting the profound impact of co-infection on immune system function. The patient's severely depleted CD4 count and the atypical CD4:CD8 ratio reflect the advanced stage of HIV infection and the superimposed TB. The findings emphasize the need for close monitoring and aggressive management of co-infected patients to mitigate the risk of opportunistic infections and disease progression. Conclusion: This case report documents a rare and severe presentation of TB/AIDS co-infection with profound immunosuppression and a reversed CD4:CD8 ratio. It serves as a reminder of the significant morbidity and mortality associated with advanced HIV and TB co-infection, particularly in cases of delayed diagnosis or suboptimal treatment adherence.